Study of the Effect of Water Injection on Successive Oil Layers - Urinov Fazliddin Najmiddin ugli (Scientific Trends, 2025)
Artificial waterflooding was also effectively carried out at the fields of the former Kyrgyzneft association, where by this time ten out of 13 developed oil reservoirs were covered by waterflooding. A great deal of work on the introduction of waterflooding was carried out during this period by the teams of the Institute of Geology and Exploration of Oil and Gas Fields (IGEOF), the Department of Development and Operation of Oil and Gas Fields of the Tashkent Polytechnic Institute, the central research laboratories of the former Fergananeft, Andizhanneft oil field administrations and the Kyrgyzneft association.
Keywords: Development system, Oil recovery factor, Reservoir pressure, Well grid, Injection well, Multilayer object, Production regulation, Fergana Oil field, Waterflooding,